Analisis Dialektika Hegel dalam “Desak Anies”: Sebuah Pendidikan Demokrasi - Edel, Eky Erlanda; Syihabuddin; Sasnitya, Raden (Universitas Pamulang, 2024)
This research aims to analyze Anies Baswedan's thinking patterns, particularly during dialogues, using Hegelian Analysis, which emphasizes the process of thesis, antithesis, and synthesis in the dynamics of social-political conflict and resolution. This study also highlights the importance of democratic education in facilitating critical and in-depth understanding of political issues. The research employs a qualitative approach with content analysis and narrative analysis methods, using Hegelian Dialectics to identify the thesis, antithesis, and synthesis in Anies Baswedan's thoughts and the